Clinical characteristics and surgical outcome of prolactinoma in patients under 14 years old. Issue 6 (February 2019) - Zhao, Yi; Jin, Di; Lian, Wei; Xing, Bing; Feng, Ming; Liu, Xiaohai; Wang, Renzhi
Abstract : Abstract: Prolactinoma is one of the most common pituitary tumors, but relatively uncommon in patients under 14 years old. Surgery is the second-line treatment for prolactinoma when patients show resistance or intolerance to medical therapy. There are only a few published series of children who underwent surgery treatment. This study is performed to investigate the clinical manifestation and surgical outcome of pituitary prolactinoma in patients under 14 years old who are resistant or intolerant to medical therapy of dopamine agonist. Thirty-six cases were included in a retrospective review of patients under 14 years old operated for prolactinoma between December 1987 and December 2015. Preoperative radiological and endocrinal evaluation was performed on every patient. All patients received operation with trans-sphenoidal approach. Based on enhanced pituitary magnetic resonance imaging (MRI) taken 2 months after the surgery, total resection was achieved in 16 patients (44.4%) and subtotal resection in 20 (55.6%). Thirty-four cases (94.4%) showed remarkable decrease of prolactin (PRL) level 7 days after surgery, and 16 (44.4%) returned to normal. All patients were followed up for 2 years. Tumor regrowth or recurrence occurred in 5 patients and secondary treatment was applied, including drug treatment in 2 patients, second surgery in 2, and radiotherapy in 1. Trans-sphenoidal pituitary surgery is an effective treatment for prolactinoma in patient under 14 years old. There is no significant difference between the patients under 14 years old and adults for prolactinoma in characteristics and treatment.